Uma Análise da Influência da Subamostragem de Crominância em Vídeos Estereoscópicos Anaglíficos - Andrade, Leonardo Antonio de; Goularte, Rudinei (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2010: Proceedings of the 16th Brazilian Symposium on Multimedia and the Web, 2010)
This paper presents an analysis on how the chrominance subsampling affects the three-dimensional perception in stereoscopic anaglyph videos. The analysis used objectives and subjectives measures of video quality, encoded by color matching red/cyan and green/magenta methods. The chrominance subsampling 4:2:2 and 4:2:0 (at color space YCbCr) was applied for each method of color combination and the results have shown that the method green/magenta is less sensitive than red/cyan method for chrominance subsampling. The analysis also demonstrates that subsampling 4:2:0 is prohibitive for both methods.